Punca infeksi Acanthamoeba spp. di kalangan pemakai kanta sentuh di Kuala Lumpur - Haliza Abdul Mutalib,; Saleha Abdul Majid,; Mohamed Kamil Abdul Ghani,; Anisah Nordin,; Yusof Bin Suboh,; Norhayati Moktar, (penerbit ukm, 2005)
The objective of this study was to determine the sources of the high incidence of Acanthamoeba infection among contact lens wearers in Kuala Lumpur. One hundred and seventy four samples were taken from 66 disposable soft contact lens wearers and they were also interviewed by using a questionnaire form. All the contact lens wearers used various types of disinfecting or multipurpose solutions to clean and disinfect their lenses. Swabs were taken from their worn contact lenses, lens storage cases and also from their remaining contact lens solutions. From these swaps a complete culture process was carried out toisolate the Acanthamoeba spp. The Acanthamoeba spp. was isolated successfully from 14 samples of 7 subjects. High yields of isolates were obtained from the lens storage cases (13.5%) and the contact lenses itself (10.6%). However, no isolation was observed from the disinfecting solutions used. The potential sources of Acanthamoeba infection were traced to the contact lenses and the lens storage cases. The oral questionnaires showed high percentage of incompliance among contact lens wearers where many used tap water for cleaning lenses and rinsing storage cases.